Embelin inhibits growth and induces apoptosis through the suppression of Akt/mTOR/S6K1 signaling cascades12. Issue 3 (9th August 2012) - Kim, Seong Won; Kim, Sung‐Moo; Bae, Hang; Nam, Dongwoo; Lee, Jun‐Hee; Lee, Seok‐Geun; Shim, Bum Sang; Kim, Sung‐Hoon; Ahn, Kyoo Seok; Choi, Seung‐Hoon; Sethi, Gautam; Ahn, Kwang Seok
Abstract BACKGROUND Akt/mTOR/S6K1 signaling cascades play an important role both in the survival and proliferation of tumor cells. METHODS In the present study, we investigated the effects of embelin (EB), identified primarily from the Embelia ribes plant, on the Akt/mTOR/S6K1 activation, associated gene products, cellular proliferation, and apoptosis in human prostate cancer cells. RESULTS EB exerted significant cytotoxic and suppressive effects on Akt and mTOR activation against androgen‐independent PC‐3 cells as compared to androgen‐dependent LNCaP cells. Moreover, EB suppressed the constitutive activation of Akt/mTOR/S6K1 signaling cascade, which correlated with the induction of apoptosis as characterized by accumulation of cells in subG1 phase, positive Annexin V binding, down‐regulation of anti‐apoptotic (Bcl‐2, Bcl‐xL, survivin, IAP‐1, and IAP‐2) and proliferative (cyclin D1) proteins, activation of caspase‐3, and cleavage of PARP. We also observed that EB can significantly enhance the apoptotic effects of a specific pharmacological Akt inhibitor when used in combination and also caused broad inhibition of all the three kinases in Akt/mTOR/S6K1 signaling axis in PC‐3 cells. CONCLUSIONS EB inhibits multiple signaling cascades involved in tumorigenesis and can be used as a potential therapeutic candidate for both the prevention and treatment of prostate cancer. Prostate 73: 296–305, 2013. © 2012 Wiley Periodicals, Inc.